PATHOGENESIS OF INFECTIOUS BRONCHITIS VIRUS IN INFECTED BROILER CHICKENS - M.H. Mohammed (Basrah Journal of Veterinary Research)
Infectious bronchitis (IB) is one of the most common viral diseases of poultry. The objective of this study was to estimate the distribution of avian infectious bronchitis virus isolate in experimentally infected chicken. Twenty-one-day-old commercial broilers were divided randomly into two groups (fifty in the experimental and twenty in the control group). Chicks in the experimental group were inoculated intranasal with 106 ELD50/0.1 mL of the virus. The samples from different tissues were collected at day 0, 3, 5, 7, 10, 15 and 20 postinoculation. Chickens showed mild respiratory signs and depression. Viral RNA was detected in the kidney, lung and tracheas. The most important clinical signs and virus finding appeared on day 1 pi. Data showed that the number of infected chickens and viral RNA detection from tissues was reduced with increasing antibody titer on day 20 pi. The results demonstrated that the IB virus has wide tissue distribution for respiratory, urogenital, and digestive systems.